Elements of Humor in the Personality of Rajendar Singh Bedi - Muhammad, Wali; Qarni, Muhammad Awais; Bashir, Sonia (sourcecoder, 2024)
Rajendar Singh Bedi is one of the famous Urdu fiction writers. Although there are elements of extreme seriousness in his short stories, but in practical life he was quite present, sharp and witty. In gatherings with friends, the attendees of the gatherings were amused by his antics and in a way felt fear that they might not be targeted by Bedi Sahib. Bedi's humor did not hurt anyone and in this case he had the courage to laugh at himself. This aspect of Bedi's personality is different from his fiction and the reason for this is that Bedi's painful heart tries to take refuge in humor in everyday conversation. In this research paper, the elements of satire and humor in Bedi's personality have been analyzed and in this regard, several incidents and the statements of his friends and contemporaries have been quoted, in the light of which this aspect of Bedi's personality has been analyzed.